2014
DOI: 10.1021/nn5017742
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Gold Nanoparticle Mediated Photoporation: Vapor Nanobubbles Outperform Direct Heating for Delivering Macromolecules in Live Cells

Abstract: There is a great interest in delivering macromolecular agents into living cells for therapeutic purposes, such as siRNA for gene silencing. Although substantial effort has gone into designing nonviral nanocarriers for delivering macromolecules into cells, translocation of the therapeutic molecules from the endosomes after endocytosis into the cytoplasm remains a major bottleneck. Laser-induced photoporation, especially in combination with gold nanoparticles, is an alternative physical method that is receiving … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
236
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 168 publications
(244 citation statements)
references
References 51 publications
7
236
0
1
Order By: Relevance
“…Note that a 1 h incubation time was selected since QD induced toxicity became too high for longer incubation times ( Figure S3). Photoporation was performed with a fixed concentration of contrast agents (2 mg/ml for FD and 1 µM for CdSe QD), but with increasing laser fluence settings (all above the vapour nanobubble generation threshold of ~1 J/cm 2 ) 43 . From the confocal images in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Note that a 1 h incubation time was selected since QD induced toxicity became too high for longer incubation times ( Figure S3). Photoporation was performed with a fixed concentration of contrast agents (2 mg/ml for FD and 1 µM for CdSe QD), but with increasing laser fluence settings (all above the vapour nanobubble generation threshold of ~1 J/cm 2 ) 43 . From the confocal images in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For a more detailed theoretical framework the reader is referred to the work by Pustovalov et al 42 . Finally, the setup has a time-response and light scattering mode to allow detection of VNB formation 43 . Finally, the relative MFI of a cell population was calculated by dividing the MFI at a certain time after labelling by the MFI of untreated cells at the same time point.…”
Section: Generation and Detection Of Vapour Nanobubblementioning
confidence: 99%
“…Traditional methods of targeted delivery of impermeable molecules into cells require microinjection using a mechanical needle or microelectrodes, which often causes cell death and compromises sterility. Carbon 28,29 and gold 30,31 nanoparticles in conjunction with pulsed 28 or continuous-wave 29 laser beams have been employed for the delivery of exogenous small molecules to cells; this approach requires the presence of the nanoparticles along with the molecules to be delivered in the vicinity of the membrane of the target cell. Furthermore, in viral delivery methods, the size of the plasmids that can be packaged for delivery is limited, which may restrict the use of these methods to the delivery of only single-opsin plasmids rather than multiple opsins (such as White-opsin).…”
Section: Resultsmentioning
confidence: 99%
“…Upon laser irradiation local perturbation effects may be due to thermal, chemical, or cavitation-mediated fluid shear phenomena. Recent efforts indicate that tuning the laser pulse parameters and properties of the absorbing particles can bias the mechanism towards a particular mode 95,96 . Although parameters are still being explored, a proof-of-concept study demonstrated conditions under which irradiation of gold nanoparticles was proposed to trigger localized thermal damage that permitted more than half of the treated cells to take up labelled antibodies 97 .…”
Section: Towards Precision Membrane Disruptionmentioning
confidence: 99%